2012
DOI: 10.1007/s10899-012-9339-4
|View full text |Cite
|
Sign up to set email alerts
|

Losing More by Losing It: Poker Experience, Sensitivity to Losses and Tilting Severity

Abstract: In poker, detrimental decision-making as a result of losing control due to negative emotions is known as tilting. Previous evidence suggests that poker experience is related to better emotion regulation in dealing with poker losses, and possibly to reduced severity of tilting in the game. A correlational on-line study (N = 417) was conducted to operationalize the tilting phenomenon by defining certain experiential characteristics that conceivably protect players from tilting or predispose them to it. These cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 17 publications
4
42
0
1
Order By: Relevance
“…The first outcome is that the effects of frustration will cause the player to become more determined in their pursuit of victory [8 & 14]. The second outcome is that the effects of frustration will cause the player to give-up, and, accepting their imminent defeat, the player will no longer make serious attempts towards victory either quitting the game then and there or continuing to play in a tokenistic fashion [17].…”
Section: Frustration As It Has Been Observed In Human Playersmentioning
confidence: 99%
“…The first outcome is that the effects of frustration will cause the player to become more determined in their pursuit of victory [8 & 14]. The second outcome is that the effects of frustration will cause the player to give-up, and, accepting their imminent defeat, the player will no longer make serious attempts towards victory either quitting the game then and there or continuing to play in a tokenistic fashion [17].…”
Section: Frustration As It Has Been Observed In Human Playersmentioning
confidence: 99%
“…Furthermore, it has been repeatedly identified that it is erroneous to consider all online gambling activities as being remotely homogenous, given the observed variation in not only the game structure but in the types of individuals that play specific games Laakusuo et al, 2014;Wood et al, 2014). At present, policy decisions surrounding online gambling - particularly in relation to problem gambling (and including problematic online poker players) - are often made by conceptualising online gambling as a single entity.…”
Section: Limitations Of Evidence Basementioning
confidence: 99%
“…Impulsivity is believed to be a core predictor of problem gambling within poker gambling (Barrault & Varescon, 2013;Laakusuo et al, 2014). It is evident from predictive modelling that online poker players that have high variation and frequency in betting, indicative of emotionally--based gambling, are more likely to self--exclude which is considered by some as a reliable proxy for problem gambling (Braverman & Shaffer, 2012) (I now have data from Unibet showing otherwise which is why I've added 'by some as').…”
Section: Risk For Harm In Poker (Offline and Online)mentioning
confidence: 99%
See 2 more Smart Citations